DC Shifts-fMRI: A Supplement to Event-Related fMRI - Li, Qiang; Liu, Guangyuan; Yuan, Guangjie; Wang, Gaoyuan; Wu, Zonghui; Zhao, Xingcong (Frontiers in Computational Neuroscience, 2019)
Event-related fMRI have been widely used in locating brain regions that respond to specific tasks. However, activities of brain regions which modulate or indirectly participate in the response to a specific task are not event-related. Event-related fMRI can’t locate these regulatory regions, detrimental to the integrity of the result that event-related fMRI revealed. Direct-current EEG shifts (DC shifts) have been found linked to the inner brain activity, a fusion DC shifts-fMRI method may have the ability to reveal a more complete response of the brain. In this study, we used DC shifts-fMRI to verify that even when responding to a very simple task, 1). The response of the brain is complicated than event-related fMRI generally revealed; 2). DC shifts-fMRI have the ability of revealing brain regions whose responses are not in event-related way. We used a classical and simple paradigm which is often used in auditory cortex tonotopic mapping. Data were recorded from 50 subjects (25 male, 25 female) who were presented with randomly presented pure tone sequences with six different frequencies (200, 400, 800, 1600, 3200, 6400 Hz). Our traditional fMRI results are consistent with previous findings that the activations are concentrate on the auditory cortex. Our DC shifts-fMRI results showed that the cingulate-caudate-thalamus network which underpins sustained attention is positively activated while the dorsal attention network and the right middle frontal gyrus which underpin attention orientation are negatively activated. The regional-specific correlations between DC shifts and brain networks indicate the complexity of the response of the brain even to a simple task and that the DC shifts can effectively reflect these non-event-related inner brain activities.